2018
DOI: 10.1007/s00266-017-1062-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Platelet-Rich Plasma and Adipose-Derived Stem Cells on Neovascularization and Fat Graft Survival

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
1
27
1
2
Order By: Relevance
“…However, only a few studies report the effects of different PRP concentrations on ADSC proliferation. Early studies found that PRP had a dose dependent effect on proliferation of ADSCs[16-18]. However, later studies had opposite opinions.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies report the effects of different PRP concentrations on ADSC proliferation. Early studies found that PRP had a dose dependent effect on proliferation of ADSCs[16-18]. However, later studies had opposite opinions.…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs are defined as a multi‐lineage stem cell population, which are isolated from the stromal vascular fraction (SVF) of adipose tissues, and can be further induced to undergo differentiation into different cells based on lineage‐specific induction factors (Bianco et al, ; Bielli et al, ). ADSC populations were featured with antigenic and neovasculogenic properties, which are thus therapeutically attractive and advantageous to widely use as seeding cells for tissue engineering and regenerative medicine (Xiong et al, ). Recently, accumulating evidence has strongly implied that several cytokines are essential to improve the survival rate of vascular endothelial cells (VECs).…”
Section: Introductionmentioning
confidence: 99%
“…Further recent studies have shown that adding PRP to a lipofilling significantly improves neovascularization and long-term fat survival. 20,21 Seyhan et al 22 explored the use of PRP with added adipose-derived stem cells in rats transplanted with fat tissue and reported that this combination enhances the survival of transplanted fat tissue. Shahzad and Mehrara 23 speculated that PRP would greatly improve fat graft survival, yet reported mixed results, some studies showing improved fat retention with PRP and others showing no such benefit.…”
Section: Discussionmentioning
confidence: 99%